Death Due To Flash Fire Accidental, Suicidal or Homicidal? - Nadeera, D.R.; Vidanapathirana, M. (My University, 2015)
Introduction: Fires involving flammable hydrocarbon liquids are called flash fires. It may span to a spectrum of mere reddening to almost total cremation of the body. The challenging problem is to determine the circumstances of the incident. The case under discussion was an almost total cremation of a mother in her house. Case report: A 51 year old mother was at home with her younger son. At around 9 am, the son noticed a fire in a room and ran away to call for help. It was extinguished in approximately 30 minutes. At the scene, a severally burnt body was found inside the severely burnt room. Almost all the goods including a plastic bucket was found burnt. The postmortem examination revealed antemortem and postmortem burns and soot in trachea and beyond. Blood was sent for gas analysis. There were no family disputes or evidence suggestive of suicide. There was no evidence of the entry of an intruder. The elder child revealed that he kept a bucket of petrol inside the room on the previous day after cleaning his motorbike. He further revealed that his mother usually lit the oil lamp in this room in the evening but in this particular morning, it may have been lit by his mother before his sister left for the O/L examination. Conclusions Evidences suggested that the burn was due to flash fire. Almost total cremation suggests homicide: According to the circumstantial evidence, this death could have been due to an accidental fire.
Keywords: Flash fire; Total cremation; Accidental fire